Analysis of the effect of the level of satisfaction of public service synergy management efforts and the status of online BPJS referral users on customer satisfaction - Johannes Sembiring; Nur Mala Sari (Universitas Aisyah Pringsewu, 2022)
The Sipultak Health Center is one of the health service centers for the community in the North Tapanuli Regency. To make public health services good, the government formed the Social Security Administering Body. The tiered referral services and online referrals implemented by BPJS are still not in line with Law No. 25 of 2009. The problem formulation of this paper is how to analyze the effect of satisfaction levels, efforts to manage public service synergies and the status of BPJS online referral users on customer satisfaction at the Sipultak Health Center. The research method is Logistic Regression Analysis. Held at the Sipultak Health Center. The research sample was 343 respondents. The results of data analysis show that there is an influence on the level of satisfaction (pValue = 0.000), there is an influence on management efforts in improving service quality (pValue = 0.000), there is a synergistic effect on public services (pValue = 0.000), there is an effect on user status (BPJS customer membership (pValue = 0.000) = 0.000), BPJS service quality (pValue = 0.000), and customer fees (pValue = 0.008)). The most dominant factor is the quality of BPJS service with OR = 24,885. It is hoped that the concept of health management which can lead to convenience for humans should be paid more attention so that it does not bring good things and is prohibited by law. Abstrak: Puskesmas Sipultak adalah salah satu pusat pelaayanan kesehatan bagi masyarakat di Wilayah Kabupaten Tapanuli Utara. Untuk menjadikan Pelayanan Publik kesehatan yang baik maka pemerintah membentuk Badan Penyelenggara Jaminan Sosial. Pelayanan rujukan berjenjang dan rujukan Online yang diterapkan BPJS masih belum selaras dengan Undang- Undang Nomor 25 Tahun 2009. Rumusan masalah dari penulisan ini adalah bagaimana menganalisa pengaruh tingkat kepuasan, upaya manajemen sinergisitas pelayanan publik dan status pengguna rujukan online BPJS terhadap kepuasan pelanggan di Puskesmas Sipultak Tahun. Metode penelitian adalah Analisis Regresi Logistik. Di laksanakan di Puskesmas Sipultak. Sampel penelitian sebanyak 343 responden. Hasil analisis data menunjukkan bahwa ada pengaruh tingkat kepuasan (pValue = 0,000), ada pengaruh upaya manajemen dalam meningkatkan mutu pelayanan (pValue = 0,000), ada pengaruh sinergisitas pelayanan publik (pValue = 0,000), ada pengaruh status pengguna (kepesertaan pelanggan BPJS (pValue = 0,000), kualitas pelayanan BPJS (pValue = 0,000), dan iuran pelanggan (pValue = 0,008). Faktor yang paling dominan adalah kualitas pelayanan BPJS dengan nilai OR = 24,885. Diharapkan sebaiknya konsep penyelenggaraan kesehatan yang dapat mengakibatkan kemudahan bagi manusia harus lebih diperhatikan sehingga tidak mendatangkan hal yang baik dan yang dilarang di dalam hukum.